The hidden arrow of Maether - Beaverson, Aiden (New York : Dell Yearling, 2002)
When she runs away from her cruel stepfather rather than be married off to a follower of the evil Rane, Linn begins to discover her own special gift and wonder if she might be one of the lysefolk, followers of the Great One about whom she has only read.
Keywords: Fantasy fiction; Fantasy